UMKM Empowerment through Training & Assistance in Preparing Simple Financial Statements at UMKM Adok Furniture - Elsa Sayyidina Aulia; Nisrina Nur Afifah; Anggi Suryadi; Chandra Ayu Pramestidewi; Muhammad Nur Afif; Joko Marsudi (Jurnal Pengabdian Masyarakat Formosa, 2023)
The implementation of community service aims to empower UMKM through training and assistance in preparing simple financial statements. This activity was carried out for UMKM actors Adok Furniture Sentul Village, Babakan Madang, on July 21 to August 23, 2023. The implementation method is socialization, training and mentoring. The result of this activity is that Adok Furniture MSME actors can understand and compile cost of goods order cards, debt cards, accounts receivable cards, cash book, raw material stock cards, income statements, statements of financial position, and notes to financial statements. Previously, UMKM actors had not prepared financial statements for their businesses. Through this training and mentoring, Adok Furniture UMKM actors can find out the right cost of goods produced and selling prices, manage accounts receivable and raw material stocks, and find out the condition of business financial performance.